An infant monitoring system with the support of accurate real-time indoor positioning. Issue 4 (2nd October 2019) - Cao, Zhipeng; Cheng, Yifan; Chen, Ruizhi; Guo, Guangyi; Ye, Feng; Chen, Liang; Pan, Yuanjin
ABSTRACT: This article presents an indoor infant monitoring system based on Android system which employs a low-cost Bluetooth Low Energy (BLE) pseudolite to accurately locate the infants in the activity indoors and timely remind the parents. It can achieve a positioning accuracy better than 2 m and effectively reduce the risk of injury to infants and young children. The performance of the proposed system, using false negative rate, false alarm rate, and alarm response time as indicators, is compared with that of the system using Quuppa as a positioning source. The experiment results show that both BLE pseudolite and Quuppa as a positioning source can basically meet the positioning accuracy for the infant monitoring system, but the BLE-pseudolite-based system provides a more cost-efficient solution.